2023
DOI: 10.1002/fsn3.3625
|View full text |Cite
|
Sign up to set email alerts
|

Street‐vended grilled beef sausages as potential vehicles of bacterial and fungal pathogens: An exploratory survey in Ho, the capital city of the Volta Region of Ghana

Banabas Nkekesi,
Priscilla Amenya,
George Aboagye
et al.

Abstract: Grilled beef sausage is a popular street delicacy in many countries, and Ghana is no exception. This study assessed street‐vended grilled beef sausages as a potential vehicle of microorganisms that present food safety risks to the general public in Ho City. Twenty grilled beef sausages were obtained from various vended locations within Ho municipality by convenient sampling and were analyzed by standard microbiological protocols for food safety followed by statistical analysis with a test of significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…It was most detected in RTE vegetable salads, cabbage, lettuce, raw beef, raw chicken, raw goat meat, “Hausa koko”, “khebab,” as well as fresh and smoked fishes, with individual prevalence ranging from 2.1% to 100%. 23 - 41 , 44 , 46 , 48 , 50 - 55 , 57 , 60 - 62 , 64 - 67 , 69 , 74 , 75 , 77 - 83 The highest prevalence (100%) was recorded in lettuce and cabbage samples from a vegetable farm in Kumasi. 26 Staphylococcus spp.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…It was most detected in RTE vegetable salads, cabbage, lettuce, raw beef, raw chicken, raw goat meat, “Hausa koko”, “khebab,” as well as fresh and smoked fishes, with individual prevalence ranging from 2.1% to 100%. 23 - 41 , 44 , 46 , 48 , 50 - 55 , 57 , 60 - 62 , 64 - 67 , 69 , 74 , 75 , 77 - 83 The highest prevalence (100%) was recorded in lettuce and cabbage samples from a vegetable farm in Kumasi. 26 Staphylococcus spp.…”
Section: Resultsmentioning
confidence: 96%
“…was the second most isolated bacterium, reported by 44% (32/72) of the studies 23 , 25 , 27 - 29 , 31 , 33 , 35 - 39 , 41 , 44 , 48 , 49 , 52 , 54 , 55 , 57 , 62 , 65 - 67 , 70 , 71 , 74 , 75 , 79 - 82 ; 19 of these 32 studies specifically reported on Staphylococcus aureus , with individual prevalence ranging from 4% to 97%. 23 , 25 , 27 - 29 , 31 , 33 , 41 , 48 , 57 , 65 - 67 , 70 , 71 , 74 , 75 , 79 , 82 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Macedo et al [64] reported counts of molds and yeast between 2.78 to 4.41 log CFU/g in hot dog sausages; these results were attributable to the pH, high water activity, and nutrient composition [65]. Likewise, Nkekesi et al [66] reported fungal counts ranging from 0.0 CFU/g to 9.83 × 10 3 CFU/g for street-vended grilled beef sausages. The presence of molds and yeasts was usually related to food contamination and the production of mycotoxins, which, in most cases, were not easy to eliminate during processing.…”
Section: Microbiological Analysismentioning
confidence: 99%